An Enzyme Electrocatalytic AGp16INK4a Immunosensor Based on Polymethylene Blue Decorated on Functional Composite Electrode. Issue 6 (19th March 2020) - Wang, Xiaoying; Gong, Miao; Li, Linyu; Lv, Liangrui; Jin, Xin; Wang, Yijie
Abstract : An enzyme electrocatalytic p16 protein (AGp16 INK4a ) immunosensor based on polymethylene blue (PMB) decorated on functional composite modified glassy carbon electrode (PG-GR-CS/GCE) is constructed successfully. The PG-GR-CS having good conductivity and large specific surface area is composed of graphene (GR) doped polycaprolactam 6 (PA6) electrospun nanofibers (PG), GR and chitosan (CS), which could serve as a stable electropolymerization substrate for increasing the amount of PMB. The active catalytic electrode (PG-GR-CS-PMB/GCE) was used as the platform for the construction of an electrocatalytic immunosensor, it can greatly increase the immobilization capacity of AGp16 INK4a capture antibody (Ab1 ), and further catch the AGp16 INK4a and horseradish peroxidase-labeled detection antibody (HRP@Ab2 ) through the sandwich immunoreaction. The PMB decorated on PG-GR-CS/GCE exhibited good electron transfer and electrochemical properties, which could apply as electrocatalytically nanomaterials. Thus, the amplified electrocatalytic response were produced by the reduction of enzymatically oxidized PMB in the presence of hydrogen peroxide via HRP. It was observed that the change of the differential pulse voltammetry of the PMB was proportional to the AGp16 INK4a ranging from of 1.0 pg ml −1 to 1.0 ng ml −1 . The detection limit was down to 0.5 pg ml −1 . The successful immunosensor provides a promising alternative to the electrocatalytic detection of various tumor markers.